FACTORS THAT INFLUENCE CONSUMERS' INTENTION TO PURCHASE ENVIRONMENTALLY FRIENDLY PRODUCTS - Eric Han; Louis Utama (Graduate Program of Universitas Tarumanagara, 2024)
This research aims to test Environmental Knowledge, Environmental Sensitivity, Subjective Norms, Attitude, and Perceived Behavior Control on West Jakarta Consumers' Green Purchase Intention. Then test Attitude as a mediator of Environmental Knowledge and Environmental Sensitivity towards Green Purchase Intention. The sample used in this research was around 160 respondents domiciled in West Jakarta who had the intention to buy environmentally friendly products and services. Data was obtained through an online questionnaire distributed via social media using non-probability sampling techniques and convenience sampling methods. Then the data collected will be processed using PLS-SEM assisted by SmartPLS version 3 software. The results obtained in this research indicate that a) Subjective Norms do not have a significant influence on Green Purchase Intention. b) Attitude has a significant influence on Green Purchase Intention. c) Perceived Behavior Control has a significant influence on Green Purchase Intention. d) Environmental Knowledge has a significant influence on Attitude. e) Environmental Sensitivity has a significant influence on Attitude. f) Environmental Knowledge has a significant influence on Green Purchase Intention through Attitude. g) Environmental Sensitivity has a significant influence on Green Purchase Intention through Attitude. This study contributes to the understanding of factors influencing green purchase intention among consumers in West Jakarta. Such as paying attention consumer subjective norms, consumer attitude in buying the green product, consumers behaviors on buying green product, and provide consumer with an understanding of environmental damage to maintain consumer green purchase intention.